ANALISIS KEPEMIMPINAN DIGITAL KEPALA SEKOLAH DAN DAMPAKNYA TERHADAP GURU PRODUKTIF DI SMK NEGERI 1 AMPEK NAGARI - Indra Jati Desrizal; M. Giatman; Yuliarma; Jonni Mardizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the school principal’s digital leadership and its implications for the performance of productive teachers at SMK Negeri 1 Ampek Nagari. A mixed-methods approach was employed by combining quantitative analysis from questionnaires completed by 12 teachers and the principal with qualitative analysis through in-depth interviews. The findings indicate a noticeable difference in perceptions between the principal and teachers, especially regarding digital infrastructure, technical support, and industry collaboration. While the principal perceives the digitalization process as progressing well, teachers believe that its implementation remains uneven and constrained by limited facilities. Triangulation of data reveals that this perception gap stems from differing role perspectives in understanding digital transformation. The study underscores the need for needs-based training, improved digital facilities, and continuous evaluation to optimize digital leadership in vocational learning environments.